The Legal Responsibility of Medics and Paramedics in COVID-19 ICUs in Iranian Law - Kaviar, Hossein; Jafari, Nasrollah; Jamali , Hooriye (Bioethics and Health Law Journal (BHL), 2026)
After the spread of coronavirus in Iran, the medical staff undertook a relentless fight against COVID-19. Unfortunately, many of the nurses and physicians exposed to the virus at ICUs have caught the disease and some of them have passed away. This brings up the questions of whether the medical staff members have any commitment to staying at work by virtue of their job contracts, how responsible they are legally in this regard and whether they can avoid the potential risks by quitting their job duties based on the rule of necessity. These issues are explored in this study through a descriptive analytical method. As the results of the study suggest, a law in the Islamic Penal Code issued in 2013 rules out the application of the rule of necessity to medical practices at COVID-19 ICUs. However, due to the unpredictability of the disease at the time of signing the contacts and thus, the lack of legal commitment to working in the current pandemic conditions, medical practitioners cannot be compelled to go on with their duties in high-risk wards. Though ethically obliged to offer services to COVID patients, they do not have to do it in legal terms; those at work now were initially employed with no documented intention of dealing with patients in COVID ICUs or in other highly infected wards. In accordance with the laws on professions, when the existence of a job commitment is a matter of doubt, the commitment is assumed to be non-existent. Despite the legal stipulations, any service given to COVID patients should be praised as an act of generosity and sacrifice.